Case Report of Synchronous Prostate, Hepatocellular, and Rectal Carcinomas and Review of the Literature - Viktoria Lamprou; Daniel Paramythiotis; Dimitrios Giakoustidis; Anestis Karakatsanis; Athanasios Astreinidis; Moysis Moysidis; Antonios Mihalopoulos; Stefanos Finitsis (Case Reports in Surgery)
Synchronous occurrence of three histopathologically distinct malignant tumors is a rare event, and there are no definitive guidelines about the optimal treatment of these patients. We report a case of synchronous prostate, hepatocellular, and rectal carcinomas and discuss our therapeutic strategy that resulted in excellent clinical results.